Detection of delay in post-monsoon agricultural burning across Punjab, India: potential drivers and consequences for air quality. (18th January 2021) - Liu, Tianjia; Mickley, Loretta J; Gautam, Ritesh; Singh, Manoj K; DeFries, Ruth S; Marlier, Miriam E
Abstract: Since the Green Revolution in the mid-1960s, a widespread transition to a rice–wheat rotation in the Indian state of Punjab has led to steady increases in crop yield and production. After harvest of the summer monsoon rice crop, the burning of excess crop residue in Punjab from October to November allows for rapid preparation of fields for sowing of the winter wheat crop. Here we use daily satellite remote sensing data to show that the timing of peak post-monsoon fire activity in Punjab and regional aerosol optical depth (AOD) has shifted later by approximately two weeks in Punjab from 2003 to 2016. This shift is consistent with delays of 11–15 d in the timing of maximum greenness of the monsoon crop and smaller delays of 4–6 d in the timing of minimum greenness during the monsoon-to-winter crop transition period. The resulting compression of the harvest-to-sowing period coincides with a 42% increase in total burning and 55% increase in regional AOD. Potential drivers of these trends include agricultural intensification and a recent groundwater policy that delays sowing of the monsoon crop. The delay and amplification of burning into the late post-monsoon season suggest greater air quality degradation and public health consequences across the densely populated Indo-Gangetic Plain.